Geochemical characteristics of upper Jurassic carbonate reservoir bitumen in the Eastern Kopeh-Dagh, NE Iran. Issue 16 (18th August 2019) - Alizadeh, Bahram; Saadati, Hossein; Tarhandeh, Elham
ABSTRACT: Geochemical characteristics of solid bitumen in Upper Jurassic carbonate reservoir are investigated. Aromatic maturity parameters indicate peak to late oil window level of maturity for the bitumen samples. Regular sterane distributions, conical variable (CV), plots of δ 13 CSat versus δ 13 CAro and Pr/ n C17 against Ph/ n C18, predominance of C23 tricyclic terpane, ratios of steranes/hopanes and C23 /C21 tricyclic terpane indicate charging from clastic-rich anoxic marine source rocks. Ratios of C29 /C30 hopane, Ts/Ts+ Tm, C24 tetracyclic terpane/C20-26 tricyclic terpanes and plot of C22 /C21 versus C24 /C23 tricyclic terpanes show influences of carbonate/marl facies. All these would throw crucial guiding light on the interpretation of the future exploration.